A Review on the Concepts of Traditional Architecture by Mulla Sadra’s Al-Hikmat Al-Mota'alie - Sheijani, Zeinab Soleimani; Sheijani, Seddighe Soleimani; Khakpour, Mojgan (Journal of Islamic Architecture, 2017)
Paying little attention to the roots of today's architecture has departed the contemporary architecture from its conceptual origins. However, the single application of traditional architecture principles does not fulfill the demands of today's life. Although by peering into the traditional Iranian architecture, principles and specific ideas implicit in the Islamic wisdom of Iran are revealed. In addition to maintaining the values of traditional architecture, a new approach to architectural design can also be achieved by recognizing and integrating these principles with the necessities of today's life. The article aims to answer whether it is possible to create a link between the traditional Iranian architecture concepts and the principles of contemporary rational architecture, similar to what Mulla Sadra, the great Persian philosopher, created between the Iranian ancient wisdom and al-Hikmat al-Masha which was solely a rational philosophy. To achieve the mentioned aim, first Mulla Sadra's intellectual structure has been studied, after modeling al-Hikmat al-Mota'alie. Then the traditional architecture has been analyzed in order to recognize its being (al-Wojud) and essence (al-Mahiyat). The priority of being has been introduced in the next step, followed by levels of being. The next pace was to discuss the structure of Mulla Sadra's thinking method in architecture. The results of study indicate that the process of communication between ancient wisdom and al-Hikmat al-Mashaexplained by Sadra can be classified in two phases, cognizing and integrating. In the stage of integration Sadra used rational reasoning to prove the issues that have been obtained through intuition and the same trend can be applied in architecture. The intuitive aspects of traditional architecture can also be presented within the framework of today's rationalist architecture in two steps, including cognizing and integrating.Â